Vibroacoustic analysis of dental air turbine noise - Wonsup Lee; Ho-Beom Kwon (Nature Publishing Group, 2022)
Abstract Objective The objective of this study is to analyze the noise mechanism of dental air turbine handpiece with vibroacoustic simulation. Materials and methods The operational part of the Gentle Silence Lux 8000B (KaVo Dental GmbH) was disassembled and scanned. The scanned data were rendered to smooth irregularities and then virtually reassembled. The rendering was 3D mesh modeled for the analysis. And, the interior void space and exterior space was mesh modeled as air layer. As per simulation input informations, the material property of steel was provided for the handpiece components. Supplied air pressure of 0.22 MPa at the inlet and static temperature of 25 °C was provided as operating conditions. Twenty virtual microphones were arrayed to measure the noise. Vibroacoustic noise simulation was performed with ACTRAN 2021 (MSC software corporation). Results The mean value of noise ranged from 49.88 to 66.38 dB while the peak value ranged from 69.53 to 81.64 dB depending on the microphone position. All microphones showed the similar noise pattern which had peak amplitude at around 4500 Hz. The calculated natural frequency of interior air layer was 4478.92 Hz and 7573.77 Hz. Discussion The simulated result showed similar tonal noise of dental handpiece suggesting air resonance phenomenon as a possible cause of dental handpiece noise. Conclusion Vibroacoustic analysis of the air layer contained within the dental air turbine handpiece showed the resonance peak noise at 4478.92 Hz under the simulated conditions.